POTENSI PENINGKATAN PRODUKSI JAGUNG DALAM MENDUKUNG KEMANDIRIAN PANGAN DI KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR - MUHLISIN Muhlisin (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2023)
Maize plants are plants that can grow in various parts of the world including indonesia. Maize is one of the most important and strategic food crops in agricultural development efforts in Indonesia because it is one of the staple crops for human needs, this makes maize very important to cultivate. Maize is the second staple food after rice. In addition, maize can also be used as a raw material in animal feed. Around 50% of maize utilization in Indonesia is used in the animal feed industry. The ever-increasing demand for maize has depleted the national maize stock, resulting in unfulfilled distribution to each region. The researcher's objective is to determine the strategy for increasing maize production in Pringgabaya District, East Lombok Regency, West Nusa Tenggara Province. Sampling was conducted using purposive sampling technique, where members were selected intentionally, namely on the strategy of increasing corn production in Pringgabaya Subdistrict by tracing the population sampled as many as 45 corn farmers. The results showed that the strategy to increase corn production in Pringgabaya Subdistrict, East Lombok Regency uses SWOT analysis and SO strategy, which is used to take advantage of existing strengths and opportunities to minimize weaknesses and threats by increasing production using superior seeds that are resistant to erratic weather changes and adopting the direction of extension workers so that corn production as food can increase.